From james stewart calculus Early Transcendentals.Before he states the proof he intoduced a property of differentiable funcion(adsbygoogle = window.adsbygoogle || []).push({});

My problem is how we defined [itex]\epsilon[/itex] to be 0 when [itex]\Delta x[/itex]=0 If y=f(x) and x changes from a to a + [itex]\Delta[/itex]x , we defined the increment of y as

[itex]\Delta[/itex]y = f(a + [itex]\Delta[/itex]x) - f(a)

Accordin to definition of a derivative ,we have

lim [itex]\frac{\Delta y}{\Delta x}[/itex] = f'(a)

so if we denote by [itex]\epsilon[/itex] the difference between Difference Qutient and the derivative we obtain

lim [itex]\epsilon[/itex] = ( [itex] lim \frac{\Delta y}{\Delta x}[/itex] - f'(a) ) = 0

But [itex]\epsilon = \frac{\Delta y}{\Delta x} - f'(a) \Rightarrow \Delta y = f'(a) \Delta x + \epsilon \Delta x[/itex]

If we Define [itex]\epsilon[/itex] to be 0 when [itex]\Delta x[/itex]=0.then [itex]\epsilon[/itex] becomes a continuous function of [itex]\Delta x[/itex]

where this is not in the Domain.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Help in proof of chain rule

**Physics Forums | Science Articles, Homework Help, Discussion**